Thromboembolic stroke in C57BL/6 mice monitored by 9.4 T MRI using a 1H cryo probe - Langhauser, Friederike; Grudzenski-Theis, Saskia; Lemke, Andreas; Alonso, Angelika; Schad, Lothar R.; Hennerici, Michael G.; Meairs, Stephen; Fatar, Marc (Experimental & translational stroke medicine, 2012)
A new thromboembolic animal model showed beneficial effects of t-PA with an infarct volume reduction of 36.8% in swiss mice. Because knock-out animal experiments for stroke frequently used C57BL76 mice we evaluated t-PA effects in this mouse strain and measured infarct volume and vascular recanalisation in-vivo by using high-field 9.4 T MRI and a 1H surface cryo coil.
Gesehen am 01.10.2018